2007
DOI: 10.4028/www.scientific.net/kem.344.461
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Filling of Die Corners in Box-Shaped Tube Hydroforming by Control of Wrinkling

Abstract: The filling of the die corner in hydroforming of a tube with a box die was improved by controlling wrinkling under oscillation of internal pressure. In this process, a small wrinkle occurs near the die corner in the former stage, and then the wrinkle is eliminated in the latter stage because the flat bulge appears in the former stage due to the oscillation of internal pressure. A hydroforming process of steel tubes with a box die was performed in both three dimensional finite element simulation and experiment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Also, Mori et al [12] proposed the idea of using pulsing pressure to improve formability in the free bulge hydroforming process of steel tube. In the following years, Loh-Mousavi et al [13,14] used this method for forming T shape and square parts and Ma et al [15] used in the manufacture of assembled camshafts.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Mori et al [12] proposed the idea of using pulsing pressure to improve formability in the free bulge hydroforming process of steel tube. In the following years, Loh-Mousavi et al [13,14] used this method for forming T shape and square parts and Ma et al [15] used in the manufacture of assembled camshafts.…”
Section: Introductionmentioning
confidence: 99%
“…For recent years, a new loading path referred as pulsating hydroforming process of tubes has been developed based on the computer accurately controlling and verified to prevent the thickness of tube wall thinning and obtain a uniform expansion, which can effectively improve the hydroformability. 4 Mori and colleagues 57 examined the mechanism of improvement of formability by experiments and simulations of tube hydroforming under monotonic increasing internal pressure and pulsating internal pressure. It was found that the occurrences of bursting and buckling were prevented by the oscillation of pressure, and the wall thickness of the formed tube was also improved by the oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…FEA was used to verify the proposed model. Loh-Mousavi et al 10 utilized pulsating internal pressure to prevent tube wrinkling and bursting in the corner filling process of a box-shaped die. Orban and Hu 11 carried out a parametric study on the effect of the coefficient of friction on the thickness distribution along the cross-section of a hydroformed tube.…”
Section: Introductionmentioning
confidence: 99%